Analiza i ocena apeli reklamowych w krajowej reklamie prasowej - Woźniczka, Jarosław (Advertising Appeals in Polish Press Advertising: The Analysis and Evaluation, 2006)
The article presents the results of the analysis of advertising appeals identified in 250 advertisements placed in Polish press in 2003. It is a part of a bigger research project dedicated to the creative strategy in Polish press advertising. The appeals were described and classified according to three basic criteria: the way of offer presentation, informational content of the message and the consumer attitude built by the advertisement. Different types of appeals were selected, including feature-benefit appeal, problem-solution appeal and image appeal, rational and emotional appeals or positive and negative appeals. Next, the quantitative analysis of the appeals was conducted and the relations between the type of advertising appeal and product category advertised were indicated.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (2); 2006; nr 1110, s. 110-118